2013
DOI: 10.1080/02640414.2013.835436
|View full text |Cite
|
Sign up to set email alerts
|

Marathon progress: demography, morphology and environment

Abstract: As opposed to many other track-and-field events, marathon performances still improve. We choose to better describe the reasons for such a progression. The 100 best marathon runners archived from January 1990 to December 2011 for men and from January 1996 to December 2011 for women were analysed. We determined the impact of historical, demographic, physiological, seasonal and environmental factors. Performances in marathons improve at every level of performance (deciles). In 2011, 94% of the 100 best men athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 30 publications
(43 reference statements)
0
33
0
Order By: Relevance
“…It is known that warm weather causes a major alteration of cardiovascular, metabolic, neuromuscular, and thermoregulatory function (Maughan et al, 2007). Consequently, it increases the risk of hyperthermia, directly affecting the central nervous system and contributing to the onset of fatigue during prolonged exercise (Marc et al, 2014). In this sense, El Helou et al (2012) observed that, the higher the temperature increase, there is a drastic reduction in the running speed and significantly increases the percentage of athletes who retire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that warm weather causes a major alteration of cardiovascular, metabolic, neuromuscular, and thermoregulatory function (Maughan et al, 2007). Consequently, it increases the risk of hyperthermia, directly affecting the central nervous system and contributing to the onset of fatigue during prolonged exercise (Marc et al, 2014). In this sense, El Helou et al (2012) observed that, the higher the temperature increase, there is a drastic reduction in the running speed and significantly increases the percentage of athletes who retire.…”
Section: Discussionmentioning
confidence: 99%
“…For example, with regards to the influence of temperature, Ely et al (2007) indicated that the best historical times in the marathon have been achieved during the early morning, with cold ambient temperatures (10-15 • C) and during the spring or autumn. In this regard, despite the high standard of competition during the summer in the Olympic Games, Continental or International Championships no world records and few good annual performances are established possibly by the temperatures during this period of year (i.e., London Olympics 2012: 27 • C, Rio Olympics 2016: 21 • C, Doha World Championship 2019: 32 • C) (Marc et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Marc et al (26) analysed running speed and BMI in 100 of the best marathoners from 1996 to 2011 and demonstrated that running speeds declined as the BMI became larger or smaller than 19.8 kg/m 2 and 18.2 kg/m 2 for male and female marathoners, respectively. The cross-sectional studies do not provide definite information about a cause-and-effect relationship between leanness and running performance.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported weight have been used for epidemiological studies (45, 46). There are anthropologic studies on using data from website (26, 47), sports magazines, compendia, or event programs (48). Given that self-reporting is the only source of weight information in this particular population, it is worthwhile to use these data to document the long-term trend and highlight the prevalence of thinness among competitive adolescent female runners.…”
Section: Discussionmentioning
confidence: 99%
“…So, considering the heart rate on the level of AeT and AT, it is worth noting that the most expressed differences are observed between asthenics (132.8 ± 6.2 and 169.5 ± 7.1 bpm) and hypersthenics (125.8 ± 6.2 and 157.5 ± 6.5 bpm) -7 and 12 bpm respectively. The ratio of the results points at the predominance of asthenics over hypersthenics on the capability of cardiovascular system functioning within the limits of aerobic energy supply, the ability to cope with significant loads during economy mode of body function (Prosser, 1994;Edward, 1995;Marc, 2014).…”
Section: Resultsmentioning
confidence: 99%